Regulation of long non-coding RNA H19 in mesenchymal stromal cells during osteogenic differentiation - Rockenbach, Dennis Michael; Justus Liebig University Giessen (My University, 2022)
In rheumatic diseases, the delicate balance between bone remodeling, formation and degradation is disbalanced by mechanical stress, inflammatory factors and other mediators. Visfatin is expressed as a pro-inflammatory adipocytokine in adipose tissue and influences osteogenic and adipogenic differentiation of mesenchymal stromal cells (MSCs). Dr. Tsiklauri from our research group was able to show, how the altered production of matrix components, matrix metalloproteinases and inflammatory mediators of differentiated osteoblasts leads to the formation of an osteoporotic bone structure. The aim of this thesis was to investigate the role of long non-coding (lnc-)RNA as a potential pathway in the regulation of osteogenesis and matrix production by visfatin. lncRNAs are RNA molecules over 200 nucleotides in length. They are transcribed and processed analogously to 'classical' messenger RNA, but are not translated into proteins. Instead, as 'RNA molecules', they directly regulate gene expression, RNA-protein interaction and other metabolic processes. In the context of osteogenesis, lncRNA H19 was of particular interest, as it was shown to be up-regulated in healthy bone in the course of osteogenic differentiation. For this purpose, MSCs from healthy donors and osteoarthritis patients from our biobank were brought to osteogenic differentiation and examined. The increased expression of H19 during differentiation described in the literature could be confirmed. When stimulated simultaneously with visfatin, this up-regulation was suppressed. Other investigated adipokines (leptin and resistin) and inflammatory mediators (TNFα) did not show this effect. H19 itself contains the micro-RNAs 675-3p and -5p in its nucleotide sequence. In the experiment, it could be shown that although 'total' H19 as well as -5p were suppressed by visfatin, whereas miRNA 675-3p was up-regulated. This demonstration of the down-regulation of lncRNA H19 and miRNA 675-5p as well as the increased expression of miRNA 675-3p can contribute to the understanding of the matrix changes in the inflammatory milieu of rheumatoid diseased bone.
Keywords: lncRNA H19; micro RNA 675-3p; micro RNA 675-5p; long non-coding RNA; MSC; Adipokines; Visfatin; Osteogenic differentiation; ddc:610